Development and Validation of a Simple-to-Use Nomogram for Predicting the Upgrade of Atypical Ductal Hyperplasia on Core Needle Biopsy in Ultrasound-Detected Breast Lesions - Huang, Yun-Xia; Chen, Ya-Ling; Li, Shi-Ping; Shen, Ju-Ping; Zuo, Ke; Zhou, Shi-Chong; Chang, Cai (Frontiers in Oncology, 2021)
Background: To develop and validate a simple-to-use nomogram for predicting the upgrade of atypical ductal hyperplasia (ADH) on ultrasound (US)-guided core needle biopsy (CNB) in patients with US-detected breast lesions. Methods: Two retrospective sets, the training set (N=401) and the validation set (N=186), from Fudan University Shanghai Cancer Center between January 2014 and December 2019 were retrospectively analyzed. Clinicopathological and US features were selected using univariate and multivariable logistic regression, and the significant features were incorporated to build a nomogram model. Model discrimination and calibration were assessed in the training set and validation set. Results: Of the 401 ADH biopsies, 66.6% were upgraded to cancers. In the multivariable analysis, the risk factors were age (odds ratio (OR) 2.739, 95% confidence interval (CI): 1.525-5.672), mass palpation (OR 3.008, 95% CI: 1.624-5.672), calcifications on US (OR 4.752, 95% CI: 2.569-9.276), ADH extent (OR 3.150, 95% CI: 1.951-5.155), and suspected malignancy (OR 4.162, 95% CI: 2.289-7.980). The model showed good discrimination, with an area under curve (AUC) of 0.783 (95% CI: 0.736-0.831), and good calibration (p =0.543). The application of the nomogram in the validation set still had good discrimination (AUC, 0.753, 95% CI: 0.666-0.841) and calibration (p =0.565). Conclusions: By incorporating clinicopathological and US features, we created a simple-to-use nomogram to predict the probability of upgrade in women with ADH. The nomogram model demonstrates good discrimination and calibration with the validation data set, which might help minimize the detection-to-treatment interval in patients who should receive surgical intervention.